Իրաքի քաղաքականությունը քրդերի նկատմամբ (1991-2003 թթ.) - Մ. Հ. Ղահրիյան (ՀՀ ԳԱԱ հրատ.)
При посредничестве США и других государств было достигнуто мирное соглашение между курдами, а программа «Нефть в обмен на продовольствие» помогла восстановлению ИК. Таким образом ситуация в курдском регионе стабилизировалась. The United States and other countries brokered a ceasefire, Washington accords were signed, the civil war ended. The Oil for Food Program helped to recover the economy. The situation in Iraqi Kurdistan gradually stabilized.
Keywords: History; Political Science; Modern History; D History; J Political Science